Control of naive and effector CD4 T cell receptor repertoires by rheumatoid-arthritis-risk HLA alleles. Issue 133 (December 2022) - Nagafuchi, Yasuo; Ota, Mineto; Hatano, Hiroaki; Inoue, Mariko; Kobayashi, Satomi; Okubo, Mai; Sugimori, Yusuke; Nakano, Masahiro; Yamada, Saeko; Yoshida, Ryochi; Tsuchida, Yumi; Iwasaki, Yukiko; et al.
Abstract: Objective: Human Leukocyte Antigen (HLA) alleles regulate susceptibility to rheumatoid arthritis (RA) and immune-mediated diseases. This study aims to elucidate the impact of HLA alleles to T cell subsets. Methods: We performed genome-wide and HLA allele association analysis for T cell receptor (TCR) beta chain repertoire in 13 purified T cell subsets from the ImmuNexUT database, consisting of 407 donors with ten immune-mediated diseases and healthy controls. Results: HLA class II alleles were associated with TRBV gene usage and the public clones of CD4 T cells, while HLA class I alleles were associated with CD8 T cells. RA-risk and immune-mediated diseases-risk HLA alleles were associated with TRBV gene usage of naive and effector CD4 T cell subsets and public clones accumulating in Th17. Clonal diversity was independent of HLA alleles and was correlated with transcriptome changes that reflect TCR signaling. Conclusion: This study revealed in vivo evidence that both HLA alleles and environmental factors shape naive and effector TCR repertoires in RA and immune-mediated diseases patients. Highlights: Risk HLA alleles regulate TRBV gene usage of naive and effector CD4 T cells. T cell receptor (TCR) public clones accumulate in Th17 cells. Risk HLA alleles regulate T cell receptor public clones of effector CD4 T cells. TCR clonal diversity are correlated with TCR signaling transcriptome changes.